Problems in the Educational Background of Arabic Language Students at the University of Jambi - Muhammad Rizky (Al-Kalimat: Journal of Linguistic and Arabic Teaching, 2025)
This study aims to analyze the educational background issues of students learning Arabic in the Arabic Language Education Study Program at Jambi University, specifically regarding the differences in initial readiness and abilities between graduates of Islamic boarding schools, madrasas, and public schools. Using a qualitative approach with a case study method, the study involved seven informants from the class of 2022 through in-depth interviews and participant observation. The results indicate that students from public schools face more significant difficulties in mastering nahwu, sharaf, and muhadatsah due to a limited Arabic language foundation and low self-confidence. Students from madrasahs demonstrated intermediate proficiency, while students from Islamic boarding schools tended to be better prepared, although they still faced challenges in communication and advanced language structures. This difference in initial abilities creates inequalities in the learning process and impacts the effectiveness of learning outcomes. The study concluded that inclusive and differentiated learning strategies, such as remedial classes and contextual approaches, are needed to accommodate diverse student backgrounds and improve the overall quality of Arabic language learning.